PERSEPSI MAHASISWA AKUNTANSI MENGENAI ETIKA PENYUSUNAN LAPORAN KEUANGAN DAN EFEK SKANDAL AKUNTANSI - budiati, Desti afeeka B2092162003 (MAKSI UNTAN, 2019)
This research aims to figure out the different perception on the ethics of financial statement writing and the scandals of accounting and business on the accounting professions between lower and higher level accounting students. The differentiating factors was determined based on the achievement of semester level and study programs taken, namely undergraduate and graduate programs. The findings of this research was based on the survey of accounting students which were divided into three sections, such as: the understanding of profit management case, the understanding of the determining factors to achieve report objectives with GCG principles which consist of misstatement, disclosure, benefit costs and accountability. The next section is a questionnaire made to find out students' understanding of accounting scandals which have an impact on the accounting professions, accounting education, and basic knowledge of accounting and business scandals.The hypothesis test used discrimination test mannwhitney. The result of the hypothesis test indicates that on the principles of financial statement writing, only the disclosure factor which has different perception between lower and higher level students. The different perception occurs on the understanding of accounting scandals on undergraduate and graduate students. Â Keywords:Â  ethics, perception, financial statement, accounting scandals, studentsÂ